Identifikasi Bakat Olahraga Bola Basket anak usia 6 sampai 10 tahun berdasarkan instrumen "I Do" Sportkompas - Irfan Oktavianus (Jurnal Sporta Saintika, 2021)
The detection of children's talents at primary school age is the first step that must be taken in the process of an achievement sports coaching program. Every child has different reasons for choosing a sport, some of them are attracted to competition and some of them who do not believe in opportunities to excel. The detection of talent for these children will be very possible to be used as a reference in the process of coaching achievement sports starting at an early age. So that later this talent detection process will make it easier to produce high-achieving basketball athletes at the regional, national, and even international levels. This research is a descriptive study that aims to describe or give a description of events or situations in a particular area. The sample in this study amounted to 22 elementary school students in the city of Padang. The test instrument used in this study was I do Sport Kompas. The data obtained in this research was quantitative data which was analyzed using descriptive statistical analysis. The results of this study revealed that of the 22 samples of the study there was only 1 sample who had aspects of basic movement skills in the category of "very good" comprehensively. 6 people were sampled in the "good" category, 7 people were sampled with the "enough" category, 7 people were sampled with the "poor" category, and 1 sample was comprehensively "less". Furthermore, if seen from the overall percentage, there are 31.81% of the sample who have skills above average, 31.82% of the sample who have average skills, and 36.37% of the sample who have skills below average. This means that of the 22 samples of the study, only 14 people were identified as above average who allowed them to be trained programmatically as early age athletes in basketball